QuickBooks online - Ringstrom, David H. (--For dummies., 2023)
QuickBooks Online For Dummies is the go-to for cloud-based small business accounting. Online accounting could be saving you time and money. Newcomers to QuickBooks Online will love this updated edition of the classic guide to making the most of mobile accounting, while accountants will appreciate the practice management features in QuickBooks Online Accountant. Dummies makes it easy to learn the program’s key features, including getting started, creating invoices and credit memos, recording sales receipts, recording and paying bills, setting up inventory items, tracking business accounts and credit cards, printing checks, processing payroll and preparing payroll tax returns, building a budget, reconciling bank accounts, generating financial reports, job estimating, billing, and tracking, backing up your data, simplifying tax preparation, and beyond. Phew! This book is perfect for small business owners, managers, and employees who utilize QuickBooks Online and would like more fluid access to their business accounting. Bookkeepers and accountants would appreciate this quintessential resource as well.